EI competencies as a related but different characteristic than intelligence - Boyatzis, Richard E.; Batista-Foguet, Joan M.; Fernández-i-Marín, Xavier; Truninger, Margarida (Frontiers in Psychology, 2015)
Amid the swarm of debate about emotional intelligence (EI) among academics are claims that cognitive intelligence, or general mental ability (g), is a stronger predictor of life and work outcomes as well as the counter claims that EI is the stronger predictor of life and work outcomes. Nested within the tempest in a teapot are scientific questions as to what the relationship is between g and EI. Using a behavioral approach to EI, we examined the relationship of a parametric measure of g as the person’s GMAT scores and collected observations from others who live and work with the person as to the frequency of his or her EI behavior, as well as the person’s self-assessment. The results show that EI, as seen by others, is slightly related to g, especially for males with assessment from professional relations. Further, we found that cognitive competencies are more strongly related to GMAT than EI competencies. For observations from personal relationships or self-assessment, there is no relationship between EI and GMAT. Observations from professional relations reveal a positive relationship between cognitive competencies and GMAT and EI and GMAT for males, but a negative relationship between EI and GMAT for females.